Analisis Risiko Kegagalan Budidaya Jamur Tiram Di Kecamatan Konda Kabupaten Konawe Selatan - Rahmanpiu, Rahmanpiu; Nia, Murni; M Hubaib, Ilhamurrahman; Nainggolan, Florentina; Rismawati, Rismawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The oyster mushroom cultivation industry demonstrates promising economic prospects in the Kendari region, yet various risk factors pose challenges that may result in harvest failures and substantial material losses. This study focuses on three primary aspects: identification of dominant risk factors hindering oyster mushroom cultivation productivity, assessment of risk exposure levels faced by farmers, and formulation of applicable mitigation approaches. The research methodology adopts a qualitative paradigm with descriptive design, implementing data triangulation through structured interviews, participatory observation, and documentation review. Respondent selection employed purposive sampling technique targeting oyster mushroom cultivation practitioners in Konda District. Research findings reveal five critical risk categories: first, biological risks encompassing parasitic fungal infestation and dipteran pest invasion; second, climatological risks including excessive atmospheric humidity and thermal volatility; third, technical operational risks covering sterilization procedure deficiencies and cultivation substrate contamination; fourth, human capacity risks related to competency limitations and technical understanding; fifth, economic risks encompassing market value fluctuations and production losses. Risk evaluation matrix indicates that biological contamination, pest organism attacks, extreme hygrometric conditions, and sanitation failures are classified within the critical risk zone. Control strategy recommendations include: intensification of sanitation and sterilization protocols, optimization of growing house environmental parameter control, implementation of integrated pest management systems, acceleration of human resource competency development, expansion of market distribution networks, and professionalization of financial management